When Schools Close Their Doors And Use The Education-technologies?. - Fassekh, Wissem; Ghalmi , Iman (sports creativity, 2023)
The year 2020 has seen a radical change, the world is surprised, by the threat of a serious disease, the COVID 19, which causes the death of all segments of society. The sequences have worsened from health to the economy, affecting all spheres of life and changing the course of human life, where we began to change our dietary, health and social habits ! The world had no weapon to face this problem and found very quickly solutions to adapt to the impact of COVID 19. Between March and July 2020, creating a phenomenon of unprecedented magnitude. By 25 March, 165 countries had closed their schools, affecting nearly 1.5 billion schools ; these numbers will grow to 194 countries and 1.725 billion pupils during the month of April, before falling again from the beginning of May 1. Terms of time and work, and in terms of organization of teaching. When the school closed its doors !.but what strategy have to adapt, to ensure the continuation of the teaching program of all categories. Using various means, including audio, visual and electronic, where most countries have adopted open distance education in terms of working time and do not show images of education or organization. The world did not have a weapon to deal with this problem and find a very flexible solution to adapt to the impacts of COVID-19. In terms of working time and pedagogical organization. Where distance learning must be integrated. Educational technology – or « Ed-Tech, » the use of hardware, software, digital content, data, and information systems in education – supports and enriches teaching and learning and improves the management and delivery of education. Educational technologies can create new connections between teachers, students, parents and broader communities to create learning networks. Investments in Ed-Tech can make education systems more resilient to future shocks and help reform and reimagine the way education is delivered.(1) - Has technology been successful in addressing this health issue ? . - What is the impact of ed-tech on education ? . - Can blended or hybrid learning replace face-to-face with the instructor ?. Keywords: Ed-tech , Hybrid-learning , schools, education system’s .